MALNUTRITION AND IMMUNE SYSTEM DYSFUNCTION, AN IMMUNOLOGICAL PERSPECTIVE: STRATEGIES FOR IMPROVEMENT OF IMMUNE SYSTEM (The Research of Medical Science Review, 2025)
This study explores the critical relationship between child malnutrition, immune system function, and susceptibility to infections. The immune system, consisting of various cells, tissues, and organs, works through innate and adaptive mechanisms to protect the body. Proper nutrition, including essential vitamins, minerals, and bioactive compounds, is crucial for maintaining immune health. Malnutrition, both undernourishment and obesity, weakens immune responses, increasing vulnerability to infections and diseases. Undernourishment, driven by factors like poverty, poor food access, and inadequate healthcare, significantly affects children's physical and cognitive development, contributing to high mortality rates. Conversely, obesity, another form of malnutrition, leads to chronic inflammation and impaired immune responses. Effective strategies to combat malnutrition include improved nutrition education, healthcare access, and community support. Addressing malnutrition's root causes, such as socio-economic disparities and food insecurity, is essential for improving global health outcomes. The WHO's guidelines on undernutrition and interventions targeting childhood malnutrition are vital steps toward alleviating the burden of malnutrition and promoting long-term health in children. This paper explores the link between Protein-Energy Malnutrition (PEM) and nutrient deficiencies, particularly in underdeveloped regions. PEM weakens immune responses, making individuals more susceptible to infections and diseases. It also highlights the need for nutritional intervention in children and HIV-infected populations. The paper also discusses the impact of micronutrient deficiencies on the immune system, particularly in HIV-infected populations and undernourished children in SubSaharan Africa. Micronutrients like selenium, zinc, magnesium, and vitamins are crucial for immune function and metabolism. The paper suggests the potential benefits of micronutrient supplementation in enhancing immune function and combating malnutrition. Further research is needed to understand the therapeutic role of supplementation in improving health outcomes in malnourished populations.